The Influence of Sound-Based Interventions on Motor Behavior After Stroke: A Systematic Review - Van Criekinge, Tamaya; D'Août, Kristiaan; O'Brien, Jonathon; Coutinho, Eduardo (Frontiers in Neurology, 2019)
Objective: To investigate the effects of sound-based interventions (SBI) on biomechanical parameters in stroke patients. Methods: Pubmed/Medline, Web of Science, Physiotherapy Evidence Database (PEDro), and Cochrane Library were searched until September 2019. Studies examining the effect of sound-based interventions on kinematic, kinetic and electromyographic outcome measures were included. Two independent reviewers performed the screening, and data extraction and risk of bias assessment were conducted with the PEDro and Newcastle-Ottawa scale. Disagreements were resolved by a third independent reviewer. Results: Of the 858 studies obtained from all databases, 12 studies and 240 participants met the inclusion and exclusion criteria. Six studies investigated the effect of SBI on upper limb motor tasks, while six examined walking. Concerning the quality assessment (Newcastle-Ottawa Quality Assessment Scale and PEDro), the nine cross-sectional studies had a median score of seven, while the randomized controlled trials had a median score of five (fair to good quality). In relation to upper limb motor tasks, only one study found improvements in cortical reorganization, increased central excitability and motor control during reaching after SBI (results of other 5 studies were too diverse and lacked quality to substantiate their findings). In relation to walking results were clearer: SBI led to improvements in knee flexion and gastrocnemius muscle activity. Conclusion: Due to the heterogeneity of the included studies, evidence was found demonstrating that SBI can induce biomechanical changes in motor behaviour during walking in stroke patients. No conclusions could be formulated regarding reaching tasks. Additionally, directions for future research for understanding the underlying mechanism of the clinical improvements after SBI are: 1) using actual music pieces instead of rhythmic sound sequences; and 2) examining sub-acute stroke rather than chronic stroke patients.